ASESMEN POTENSI RISIKO BENCANA LONGSOR TEBING SUNGAI WINONGO HILIR - Harsanto, Puji; Muzlifa, Rika; Faizah, Restu; Nursetiawan, Nursetiawan; Wisnulingga, Bayu Krisna (Politeknik Negeri Semarang, 2024)
The Winongo River is one of the rivers in the Special Region of Yogyakarta, with itssource originating from Mount Merapi. This poses various disaster risks in theWinongo River, such as flooding, debris flow, and riverbank landslides. Thisresearch focuses on analyzing disaster risks in the downstream area of the WinongoRiver, which includes the villages of Sabdodadi, Patalan, Sumbermulyo, Mulyodadi,Sidomulyo, and Donotirto. Data collection was carried out using cluster samplingand Geographic Information Systems (GIS) for each village due to the wide areacoverage. The collected data was then analyzed using the Analytical HierarchyProcess (AHP) method to determine the level of disaster risk. The results of thisstudy show that the downstream area of the Winongo River has a moderate disasterrisk level for the villages of Sabdodadi, Patalan, Sumbermulyo, and Donotirto, anda low disaster risk level for the villages of Sidomulyo and Mulyodadi. The capacityparameter significantly influences the level of disaster risk, and based on thevulnerability analysis, this is due to the presence of retaining walls on theriverbanks, which can reduce disaster risks in the Winongo River